Diagnostic yield in victims of sudden cardiac death and their relatives. Issue 6 (20th April 2020) - Hansen, Benjamin Lautrup; Jacobsen, Elisabeth Mütze; Kjerrumgaard, Amalie; Tfelt-Hansen, Jacob; Winkel, Bo Gregers; Bundgaard, Henning; Christensen, Alex Hørby
Abstract: Aims: International guidelines recommend cardiogenetic screening in families with sudden cardiac death (SCD) if the suspected cause is an inherited cardiac disease. The aim was to assess the diagnostic yield of inherited cardiac diseases in consecutively referred SCD families. Methods and results: In this single-centre retrospective study, we consecutively included families referred to our tertiary unit between 2005 and 2018 for screening due to SCD. Following evaluation of premortem medical records and postmortem findings for the proband, the families underwent a guideline-based screening protocol. Relatives were followed and cardiovascular events registered. In total, 304 families with 695 relatives were included. In probands, mean age at death was 39 years (75% males) and in relatives mean age at screening was 35 years (47% males). The proband-diagnosis was established through autopsy findings ( n  = 89), genetic analyses ( n  = 7), or based on premortem findings ( n  = 21). In the remaining 187 families with borderline/no diagnosis in the proband, screening of relatives yielded a diagnosis in 26 additional families. In total, an inherited cardiac disease was identified in 143 out of 304 families (47%). In relatives, 73 (11%) were diagnosed. Arrhythmogenic right ventricular cardiomyopathy ( n  = 16) was the most common diagnosis. During follow-up (mean 5.5 years), a low rate of serious cardiac events was observed (no SCD events). Conclusion: Forty-seven percent of SCD families were diagnosed. Eleven percent of the screened relatives received a definite diagnosis and were offered treatment according to guidelines. A low rate of serious cardiovascular events was observed among SCD relatives.